DOS CONFLITOS COM ’ĀRĀM AO DEUS DE ḪA-LA-AB: A Formação do Campo Religioso e a Elaboração do Yhwh no Yiśrā’ēl Norte na Idade do Ferro II - SANTOS, JOÃO BATISTA RIBEIRO (2018)
This research aims to reconstruct, through the inscribed and artifactual sources, the events that are in the background of the formation of the religious field of the Yiśrā’ēl North. The religious complex and functions of religion are part of the processes of cultural interactions in the ancient Near East that decisively influence the ways of being Israelites in the first half of the IX century. The formative epoch of the identities of the North Yiśrā’ēl (c. 1020–722/721) may be dated in this century, specifically in the period of the Omride dynasty (‘Omrî, 884– 873), which inaugurates in the south of the Levant the great cities and palaces. In this region, the conflicts become more serious when Šulmānu-ašaridu occupies, with its garrisons, territories siro-euphrates. Internally, Yēhû’ operates a coup d’État (841), then submits to the Assyrian king renouncing the Israeli leadership which, some four years later with the return of the Assyrian garrisons, will be occupied by the aramita Ḥăzāh’ēl. The coup is a political-military action against the cultural interactions and material connections initiated by the king ‘Omrî; with the taking of power by Yēhû’, won the divinatory project of submission to the empire and Ša-imērīšu. Regionally, Ḥăzāh’ēl in Ša-imērīšu and Meša‘ in Mô’āb demonstrated that in their program was the appropriation of Israeli towns, because the wars against the former ally. The losses of the Yiśrā’ēl North coincided with its political isolation, but the gains from the cultural interactions of the Omride Period remained and materialized with historical testimonies the religious field and the divinity. It is in this period that the god Yhwh, known in the north of the Levant and in Anatolia since the second millennium, passes by mutation among the Israelites to naturalize with the weapons and wars of the god ħalabine Haddu, source of the hybridization with the god Ba‘al in Ú-ga-ri-it. With this iconographic embodiment of Yhwh, the divine factor of male fertilization, which had already annexed the factor of fertilization of soil, cattle, and women, has become a traditional support. The inextricable royal patronage of the gift of protection is now strongly valued: Yhwh gains one mountain and becomes a warrior, one of Haddu.